Multiple Congenital Anomalies in a Patient with Interstitial 6q26 Deletion - Puvabanditsin, Surasak (Mol Syndromol, 2020)
We report a preterm male neonate presenting with a lumbosacral meningomyelocele, type II Arnold Chiari malformation, hypoplasia of the aortic arch, bicuspid aortic valve, ventricular septal defect, secundum atrial septal defect, multicystic dysplastic kidney, and hydronephrosis. Analysis with whole genome SNP microarray revealed an interstitial deletion of about 237 kb in chromosome 6q26. Long contiguous stretches of homozygosity (>3 Mb) were seen in 18 chromosomes with a total genomic size of 219 Mb. The phenotype seen in our patient has not been reported in association with the genes in the homozygous regions. However, our patient shares many phenotypic features with other reported cases that have shown a deletion in the same region of chromosome 6.